Dependence of electrical conductivity on Bi₂Se₃ thin film thickness - Menshikova, S. I.; Rogacheva, E. I.; Sipatov, A. Yu.; Fedorov, A. G. (Institute for Single Crystals, 2017)
Effect of film thickness d on electrical conductivity σ of n-Bi₂Se₃ thin films (d = 25-420 nm) prepared by thermal evaporation in vacuum onto glass substrates was investigated. It was established that the electrical conductivity increases with increasing of the thin films thickness. The observed effect is explained as a manifestation of the classical size effect connected with diffuse scattering of electrons at the thin film interfaces. The experimental σ(d) dependence is satisfactorily described using the Fuchs-Sondheimer theory for the film thickness d > 60 nm. The specularity parameter and value of electrons mean free path are determined based of the experimental data.
Залежність електропровідності від товщини тонких плівок Bi₂Se₃